Mandibular nerve fascicular cross-face for sensitive recovery after mandibulectomy: A new technique. Issue 3 (June 2013) - Gennaro, Paolo; Gabriele, Guido; Della Monaca, Marco; Facchini, Arianna; Mitro, Valeria
Abstract Trigeminal nerve damage after mandibulectomy is a condition that may occur not infrequently when oncologic resections of the maxillo-facial district are performed. In the last decades microsurgery has made possible effective osteomuscular reconstructions using vascularised free flaps. Nevertheless, this procedure, if assuring satisfactory results, involved the sacrifice of the mandibular nerve. Nowadays, supramicrosurgical innovation has shifted the gold-standard to a higher level, allowing the complete sensitive recovery after mandibulectomy. The cross-face nerve transfer technique is an innovative procedure that provides excellent nerve regeneration in mini-invasive operations, avoiding visible scars and any deficiency in donor sites. We suggest that the cross-face nerve transfer is the surgical modality of choice to restore lower lip and chin sensibility after mandibulectomy.